Balancing axes of gas turbine in electric power plant by using effective vector way (Damascus University Journal for engineering sciences, 2025)
The balancing of masses in the machine aims to eliminate and reverse inertial forces and inertia moments, as the resultant inertial forces and inertia moments affecting the gas turbine bearings are transmitted to the turbine structure and cause dynamic reactions to be incited on its points of support, causing vibrations with negative repercussions on its performance and its stability. These inertia forces are called vibration forces, and it is necessary to reduce these forces by isolating them or mitigating their effect on the turbine.The performance of the gas turbine can be improved by reducing the vibrations on its bearings, especially the vibrations resulting from the imbalance of the rotating parts that make up the turbine, by using modern techniques (the effective beam method) to achieve the economic and high technical factors of the machines, maintain the continuity of production and extend their operational life. In addition to Presenting basic principles of the dynamic balancing process of gas turbines on site in order to increase practical experiences in this field to solve these problems.
Keywords: gas turbines; balance; vibration; effective factor